EFFECTS OF MOOD STATES ON WORKING MEMORY AND BRAIN HAEMODYNAMIC RESPONSE USING OPTICAL TOPOGRAPHY MODALITY - FENG, YING XING (2015)
Higher cognitive brain functions such as language, planning and problem solving require the working memory (WM), a temporary buffer that stores limited amount of information for immediate manipulation. Studies have shown that negative mood states impair the WM functions, related to activations at the prefrontal cortex (PFC) region. However, findings reported from non-verbal and verbal WM tasks using various brain imaging modalities and experimental protocol designs are found to be inconsistent.